Prevention of Dental Caries - Hamid, Ali Maki Mahid; Nanobashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2016)
Dental caries is the scientific term for tooth decay or cavities. It is caused by specific types of bacteria. They produce acid that destroys tooth's enamel and the layer under it, the dentin. many different types of bacteria normally live in the human mouth. They build up on the teeth in a sticky film called plaque. This plaque also contains saliva, bits of food and other natural substances. It forms most easily in certain places. early caries may not have any symptoms. Later, when the decay has eaten through the enamel, the teeth may be sensitive to sweet, hot or cold foods or drinks. Caries in its early stages can be stopped. It can even be reversed. Fluorides and other prevention methods also help a tooth in early stages of decay to repair itself. White spots are the last stage of early caries. There is one way you can prevent cavities is by reducing the amount of plaque and bacteria in your mouth. Importance of prevention: better than cure. Prevention is cheaper than cure. Prevention of a disease is greater good in life than its cure. Knowledge of dental caries prevention and its application among dental practitioners is one of the main aspects for the effectiveness in the provision of preventive measures. Evaluate the application of preventive measures in regards of knowledge and impediments in dental caries prevention and the provision of oral health care services. Etiological factors of dental caries: Host factors (demographic factors) , microbial agents, environmental factors. Types of dental caries: Pit and fissure caries, proximal caries, cervical caries, root caries. Methods of caries prevention: primary prevention (methods of plaque accumulation control), Secondary prevention (at the early stage of appearing carious spots – reminarilazation therapy), Tertiary prevention (do not allow caries pathological process spread deeply in the tooth tissues. Make tooth restoration, change damaged restorations, fix toothlessness – to maintain normal functioning and self-cleaning of dental arches). Methods: Home oral hygiene tools, mechanical methods, chemical methods, nutritional methods, professional hygiene, scaling, sealing. Chemical, mechanical, and nutritional methods are used during these levels. A vast number of chemical substances have been proposed for the purpose of controlling dental caries Ideal properties. Chemical measures include: Substances which alter the tooth surface or structure. (Fluorides & Iodides). Substances which Interfere with carbohydrate degradation through enzymatic alteration. (Vitamin K). Substances which Interfere with bacterial growth and metabolism.(Anticariogenic Agent). Mechanical methods include; Tooth brushing. Interdental cleaning aids . Disclosing agents. Detergent foods. Salivary stimulants. Pit and fissure sealants. Nutritional measures advocated for the control of dental caries is restriction of refined carbohydrate intake. Other measures include Avoiding sugar that retains of teeth surface. Avoiding sugar in between meals. Eating of phosphated diets.